Dracaena fragrans 'Massangeana' Corn Plant, Fragrant Dracaena - Edward Gilman (EDIS, 2007)
This document provides a detailed overview of the Dracaena fragrans ‘Massangeana’, commonly known as the corn plant or fragrant dracaena. It describes the plant’s physical characteristics, including its upright, multiple unbranched stems, and broad evergreen leaves with a central yellow stripe. The corn plant is suitable for low-maintenance container culture or specimen planting and can grow up to 15 feet tall. It thrives in shaded areas and is moderately drought-tolerant, preferring organic soil. The document also highlights the plant’s fragrant flowers, which bloom periodically throughout the year, and its sensitivity to pests and diseases such as mites, thrips, leaf spot diseases, and root rot. Propagation is typically done through tip cuttings. Original publication date October 1999.